Modern therapy for inflammatory bowel disease - Novaković Aleksandra (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Inflammatory bowel disease (IBD) is an idiopathic chronic disease. According to the latest data, about 2.5 million people in Europe, as well about 8 thousands in Serbia, have IBD. The main symptoms of this disease are diarrhoea, abdominal pain, bleeding, anaemia and weight loss. The two major form of IBD are ulcerative colitis and Crohn's disease. There is no drug that would lead to complete healing of IBC. The goals of the therapy include introducing remission, maintaining remission, minimizing side effects of drugs and improving the quality of life. The IBC therapy includes the use of drugs such as: aminosalicylates, glucocorticoids, immunosuppressants, and biologics. As an initial therapy in the treatment of ulcerative colitis, aminosalicylates are the most commonly used, and maintenance therapy is recommended for all patients. Drugs of the first choice for maintenance of remission are also aminosalicylates. For the treatment of Crohn's disease, first-line drugs are glucocorticoids. Maintenance therapy is not mandatory for all patients with Crohn's disease. If maintenance therapy is necessary, immunosuppressors (azathioprine or methotrexate), as well as biologic agents (anti-TNF drugs or anti-integrin medications), are used.